Ecophysiology of tropical crops - Alvim, Paulo de T.; Kozlowski, T. T. (Theodore Thomas), 1917- (Academic Press, 1977)
Ecophysiology of Tropical Crops covers the knowledge and opinion on ecophysiology of the major tropical crop plants. The book discusses the fundamental ideas about the numerical description of plant development and considers effects of climatic factors (e.g., temperature, light, and water) on physiological processes in plants. The text also presents an overview of the physical and chemical characteristics of tropical soils. The ecophysiology of the major crop plants, particularly those suitable for the wet tropics, including rice, sugarcane, pineapple, grasslands, root crops, sweet potato, co.